(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the knowledge about pre-eclampsia and propose some solutions to improve knowledge about pre-eclampsia of pregnant women were treated at the Obstetrics and Gynecology Department at Bach Mai Hospital in 2023.Research methods: The cross-sectional description on 68 pregnant women. Using the questionnaire to assess knowledge about pre-eclampsia.The results: The age over 35 years old was 66.2%; gestational age over 20 weeks accounted for the majority with 95.6%. 88.2% pregnant women were provided with information about pre-eclampsia and 69.1% received information at the hospital, 66.8% pregnant women who answered correctly about general knowledge. 55.2% pregnant women answered correctly with symptom. Up to 77.9% pregnant women incorrectly answered 2 or more symptoms. 54.7% pregnant women had correct answers about preventive measures. The highest percentage of general knowledge about pre-eclampsia was 70.6% and the lowest percentage of knowledge about preventive measures was 55.9%. Conclusion: In general, the research subject understood and updated a fair level of information about pre-eclampsia. However, to help them minimize complications and have a healthy pregnancy, they still need attention and conselling of health providers and media channels.